Seismic Effect of the Offshore Structure Under Different Earthquake Loadings - Kee, T. K.; Cheok, C. J.; Amzar Kamarudin, M.A; Ahmad, Saffuan Wan; Suryanti, Reni (International Journal of Integrated Engineering, 2023)
Peninsular Malaysia is most affected by the distant Sumatra subduction zone earthquake. Meanwhile, Eastern Malaysia was subjected to major Philippine and Indonesian earthquake. Most of the offshore platform is at Terengganu, Sabah, and Sarawak. More than 65% of the offshore platform structure exceed the range of design between 20-30 years. This research aims to determine the vulnerability and risk analysis for the existing 3-legged offshore platform under earthquake load, study the behaviors of an offshore platform under major or minor earth-quake loading, and study the dynamic characteristic of an offshore platform. SAP 2000 is use to analyses and modelling the 3-legged offshore platform. In SAP 2000, the response spectrum, time history, and free vibration will be performed. The mixed load of the platform consists of dead load, imposed load, environment loads, and earthquake load. The position of the offshore platform has referred to American Petroleum Institute (API) standard. The major earthquake under off-shore platform is El-Centro and the minor is Aceh compared to time history. Based on this study, Malaysia can withstand this low seismic activity, overall joint acceleration, velocity and displacement.